Особенности совершенствования прав и обязанностей органов опеки и попечительства в Республике Узбекистан - Чopиeвa Хуpшидaбoну Хуppaм кизи (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article analyzes the issues related to improving the rights and responsibilities of guardianship and trusteeship authorities. It examines the norms concerning these authorities' rights and responsibilities in the legislation of the Republic of Uzbekistan, as well as scientific views and the experience of other countries. Based on this analysis, the article develops scientific and practical proposals for improving activities in this area.